2021
DOI: 10.1021/acs.iecr.0c05862
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Mechanism Study on Simultaneous Removal of 1,2-Dichlorobenzene and NO over MnOx–CeO2/TiO2 Catalysts at Low Temperatures

Abstract: To solve the multiple air pollution problems caused during waste incineration, simultaneous control of chlorinated aromatic pollutants (e.g., chlorobenzenes, chlorophenol, and dioxins) and nitrogen oxides (NO x ) is of great significance. Titanium dioxide-supported manganese–cerium composite oxide (MnO x –CeO2/TiO2) catalysts with low-temperature activities were prepared and applied for simultaneous abatement of 1,2-dichorobenzene (o-DCBz) and NO. The interaction mechanism between o-DCBz catalytic oxidation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…As for Figure b, the O 1s XPS spectra could be fitted to two peaks, in which the peak around 530.2 eV was attributed to lattice oxygen (denoted as O β ) and the one around 531.7 eV was ascribed to chemically adsorbed oxygen (denoted as O α ) on the catalyst surface. , The order of the O α content was 3Fe-VMT ≈ 5Fe-VMT > 7Fe-VMT > 9Fe-VMT > 1Fe-VMT > VMT, which was in accordance with the CB conversion result. Researches have revealed that the oxidative degradation of CB could be explained by the MvK mechanism: the adsorbed CB molecules were oxidized by adjacent chemisorbed oxygen on the catalyst surface, generating surface oxygen vacancies, and the consumed chemisorbed oxygen was then replenished via the dissociation adsorption of oxygen in the atmosphere on oxygen vacancies . Hence, the increase of surface chemisorbed oxygen content was the primary factor for the significant improvement of CB catalytic degradation progress, and the loading of 3 wt % FeO x strongly facilitated the CB oxidation ability of the catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…As for Figure b, the O 1s XPS spectra could be fitted to two peaks, in which the peak around 530.2 eV was attributed to lattice oxygen (denoted as O β ) and the one around 531.7 eV was ascribed to chemically adsorbed oxygen (denoted as O α ) on the catalyst surface. , The order of the O α content was 3Fe-VMT ≈ 5Fe-VMT > 7Fe-VMT > 9Fe-VMT > 1Fe-VMT > VMT, which was in accordance with the CB conversion result. Researches have revealed that the oxidative degradation of CB could be explained by the MvK mechanism: the adsorbed CB molecules were oxidized by adjacent chemisorbed oxygen on the catalyst surface, generating surface oxygen vacancies, and the consumed chemisorbed oxygen was then replenished via the dissociation adsorption of oxygen in the atmosphere on oxygen vacancies . Hence, the increase of surface chemisorbed oxygen content was the primary factor for the significant improvement of CB catalytic degradation progress, and the loading of 3 wt % FeO x strongly facilitated the CB oxidation ability of the catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…(2) The second view is that CBCs chemically adsorb on the surface acid site (Mn m+ ) by chlorine extraction to form phenolate intermediates at the start. 18,37,[50][51][52] The distinguished steps can be described as follows.…”
Section: Mechanism On Mn-based Catalystsmentioning
confidence: 99%
“…45 However, another view suggests that CB adsorption occurs mainly at oxygen vacancies (in combination with the MvK mechanism), which can accelerate the activation of reactive oxygen species and accelerate the oxidation rate. Oxygen vacancies are increased mainly by introducing metal oxides 50,56,87 or constructing special morphologies 37,125 to introduce defects and oxygen vacancies.…”
Section: Accelerating the Dechlorination Process Of Cbcs Moleculementioning
confidence: 99%
See 2 more Smart Citations